PENGARUH INVESTASI DAN PENDANAAN TERHADAP NILAI PERUSAHAAN PADA SEKTOR KABEL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hutapea, Defi Nafalia; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The main goal of the company is to maximize the welfare of stakeholders, this can be achieved by maximizing the value of the company. But sometimes companies fail to increase the company's nialai, which is one of the causes is less carefully the company in applying the factors that affect the value of the company. This makes the company's performance is viewed poorly by its stakeholders. This study aims to examine the factors that affect the value of the company that can be seen from investment and funding. The sample of this research is 6 cable sector companies listed in Indonesia Stock Exchange, which has published its financial report from year 2011-2015. The method of analysis in this study using simple and multiple regression analysis. Simple regression analysis test used to see the partial influence of investment and funding included as independent variable in this research to company value. Multiple regression analysis test to see simultaneous influence of investment and funding included as independent variable in this research to company value. The result of this research is that (1) PER investment has no posif influence and significant to company value. (2) DER funding has a positive and significant influence on firm value. Then the result of the regression estimation shows the predictive ability of the three independent variables to the company value. 58.4%, while the remaining 41.6% influenced by other factors outside the model that is not included in this analysis. Keywords: Corporate value, funding, investm